Legislation Impediments in Reorganising Government Bodies in Indonesia - Mas Pungky Hendra Wijaya; Mohammad Zulfikar Ali (BESTUUR, 2021)
Indonesia has implemented administrative reforms in a variety of areas, including reorganizing the structure of ministries and agencies. However, that effort has not yet yielded a significant outcome. The complex legal framework is believed to be primary challenge of this reform. This study aims to identify and analyze to what extent that the legislative constraints affect the reorganization attempt. This study applies qualitative approach. Data was collected through a desk-based study of legislations, policies, and secondary literatures related to bureaucracy reform in Indonesia, as well as its political and legal issues. The study's findings indicate that the government's sprawling and large structure is the result of overlapping function of laws and regulations. This hindered any efforts to reorganize. This further contributes to the administration's ineffectiveness and inefficiency. This study affirmed that legislation impedes the reorganization process because numerous laws have been used (improperly) to create a new ministry or agency rather than to reorganize.